Robotic and Autonomous Systems for Resilient Infrastructure. ([2017]) - (Professor of robotics), Richardson, Robert; Fuentes, Raul; (Writer on infrastructure), Chapman, Tim; (Employee of Kier Services), Cook, Michael; Scanlan, James P (James Patrick), 1958-; Zhibin, Li
No abstract available